2014
DOI: 10.1186/s13059-014-0435-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiles in progression to in situand invasive carcinoma of the breast with impact on gene transcription and prognosis

Abstract: BackgroundDuctal carcinoma in situ (DCIS) of the breast is a precursor of invasive breast carcinoma. DNA methylation alterations are thought to be an early event in progression of cancer, and may prove valuable as a tool in clinical decision making and for understanding neoplastic development.ResultsWe generate genome-wide DNA methylation profiles of 285 breast tissue samples representing progression of cancer, and validate methylation changes between normal and DCIS in an independent dataset of 15 normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 52 publications
9
95
0
Order By: Relevance
“…33 In this study, 10% of the DM CpGs were significantly correlated with the gene expression. This figure is similar to previous genome-wide studies in primary fibroblast samples (8.9%), 34 ductal carcinoma in situ (DCIS) of the breast (10.5%) 35 and considerably higher than other studies in breast tumors (The Cancer Genome Atlas (TCGA) breast cancer data set) (3.3%) (35). Taken together, these data suggest that associations of methylation to gene expression vary by tissue type.…”
Section: Discussionsupporting
confidence: 89%
“…33 In this study, 10% of the DM CpGs were significantly correlated with the gene expression. This figure is similar to previous genome-wide studies in primary fibroblast samples (8.9%), 34 ductal carcinoma in situ (DCIS) of the breast (10.5%) 35 and considerably higher than other studies in breast tumors (The Cancer Genome Atlas (TCGA) breast cancer data set) (3.3%) (35). Taken together, these data suggest that associations of methylation to gene expression vary by tissue type.…”
Section: Discussionsupporting
confidence: 89%
“…In view of these findings, the analysis of such a gene panel through quantitative methylation might represent a tool for predicting disease progression. These data have been confirmed by Fleischer et al who recently reported the DNA methylation profiles of a breast cancer progression series, including normal breast tissue, DCIS, invasive carcinoma, and mixed lesions [54]. In agreement with previous studies, most of the aberrations in the epigenetic profile were observed already in the pre-invasive stage.…”
supporting
confidence: 86%
“…Recently, Fleischer and colleagues also investigated methylation patterns during progression of breast cancer [54].…”
mentioning
confidence: 99%
See 2 more Smart Citations